Prosthetic articulating spacers as a preferred option for two-stage revision arthroplasty in chronic periprosthetic joint infection - Jiamin Lin; Hongyan Li; Yang Chen; Haiqi Ding; Qijin Wang; Jianhua Lv; Wenbo Li; Wenming Zhang; Xinyu Fang (Arthroplasty)
Abstract Purpose The study aimed to compare the infection control rates, mechanical complications, and functional outcomes between prosthetic and cement spacers in two-stage revision arthroplasty for chronic periprosthetic joint infection (PJI). Patients and methods Data from patients treated for chronic PJI in our center from 2014 to 2023 were retrospectively collected and the patients were divided into the prosthetic spacer (PS) and cement spacer (CS) groups based on the type of spacer used for the first-stage surgeries. Data on patients’ demographics and clinical scores were harvested. Infection control rates and mechanical complications were compared between the two groups by using chi-square tests and log-rank analysis. Results The study involved 113 cases, with a mean age of 64 ± 11.45 years (range, 31–88 years), with 48 cases in the PS group, 65 in the CS group, and all patients were followed up for at least 1 year (average 52.68 ± 26.07 months). Five patients in the PS group (10.42%) and six in the CS group (9.23%) developed recurrent infections, with no significant difference found in infection control rates (P = 0.833). The joint function score after the first-stage surgeries was higher in the PS group than in the CS group (P = 0.021). The incidence of mechanical complications, including dislocation, spacer fracture, and periprosthetic fracture, was significantly lower in the PS group than in the CS group (P = 0.024). The proportion of patients who underwent second-stage surgeries was lower in the PS group than in the CS group (58.3% vs 70.77%, P = 0.169). Conclusion For most patients with chronic PJI, PS can be used as the preferred option for two-stage revision arthroplasty.